Norman Fairclough’s Critical Discourse Analysis: The Moral Identity of the Poor Community in the Short Story Anthology Paron - Putri, Salsabila Kanina; Astuti, Eka Yuli (Universitas Nusantara PGRI Kediri, 2025)
This study aims to reveal the moral identity of the poor community as represented in two short stories from the anthology Paron by Poerwadhie Atmodihardjo using Norman Fairclough’s Critical Discourse Analysis (CDA) approach. A qualitative method with content analysis was employed, focusing on two short stories entitled Kikis (Fragmen Urip) and Wekasane Krisis. The analysis was based on Fairclough’s three-dimensional model: textual, discursive, and socio-cultural practices. The findings show that the moral identity of the main character reflects internal conflict, indecisiveness, moral deviance such as gambling and corruption, and resignation to social conditions. The production of texts illustrates the author’s background as a Javanese society member who embeds social criticism through the use of metaphors and culturally nuanced diction. Text consumption indicates the potential for reader reflection on the depicted reality. The implication of this study highlights that literary works in regional languages like Javanese short stories (cerkak) can serve as a representative medium to critically explore the crisis of moral identity and the socio-cultural dynamics of the poor community.